A method for structural and chemical regulation of negative electrode carbon materials for rate-controlled sodium ion batteries and its application

Through multi-stage heat treatment and active gas modification treatment, a sodium ion battery negative electrode carbon material with rich pore structure and surface heteroatom doping was prepared, which solved the problem of insufficient sodium storage capacity and rate performance in the prior art, and achieved high efficiency electrochemical properties of sodium ion batteries.

CN118619253BActive Publication Date: 2025-01-03BEIJING UNIV OF CHEM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410799034.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-01-03
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials have shortcomings in terms of sodium storage capacity and rate performance. In particular, the small spacing between the graphite layers of coal-based carbon materials is not conducive to the storage of large-sized sodium ions, and the larger pore structure of the coconut shell carbon materials is not It is conducive to the storage of sodium ions and leads to poor electrochemical performance.

Method used

Using a multi-stage heat treatment method, the first stage is used to remove volatile components, the second stage is to perform structural etching and surface chemical modification in the active atmosphere, and the third stage is to perform microstructure and conductivity regulation under an inert atmosphere, and to prepare the Carbon materials rich in pore structure and surface heteroatom doped carbon materials, used in the negative electrode of sodium ion battery. The specific steps include initial carbonization under the protection of argon, replacing it with active gas for modification, and then carbonizing it at high temperature, and etching and doping with heteroatomic active gases such as N, O, S, and constructing excellent carbon materials. .

Benefits of technology

Achieve high sodium storage specific capacity of 388.97mAh g-1 and Coulomb efficiency of more than 90%, showing excellent rate performance and cycle stability. The first discharge specific capacity is still 300mAh g after cycling for 200 cycles under a high current density of 1Ag-1. The discharge specific capacity of about -1 meets the needs of large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118619253B_ABST
    Figure CN118619253B_ABST
Patent Text Reader

Abstract

A method for structural and chemical regulation of rate-type sodium ion battery negative electrode carbon materials and its application, which belongs to the field of sodium ion battery negative electrode materials. At a certain temperature, the carbon material is etched and doped with an active gas. The etching is reflected in the reaction between the active gas and the carbon atoms. This process is accompanied by the introduction of non-carbon heteroatoms to obtain the negative electrode carbon material for the sodium ion battery. The present invention uses a series of active gases for etching to construct a rich pore structure. At the same time, the introduction of heteroatoms such as N, O, and S can regulate the surface chemical properties of the carbon material. Through the synergistic effect of the pore structure and surface chemistry (atomic doping), the carbon material achieves a high sodium storage capacity of 388.97 mAh g ‑1 , at 1 A g ‑1 High current density conditions showed a capacity of about 340 mAh g ‑1 It has an ultra-high specific capacity and exhibits excellent cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of negative electrode carbon materials for sodium ion batteries, and specifically relates to a structure and chemical regulation method of negative electrode carbon materials for rate-type sodium ion batteries and applications thereof. Background Art

[0002] Clean and renewable energy sources such as solar energy and wind energy have disadvantages such as intermittency and regionality, and large-scale energy storage technologies need to be developed for energy storage and transportation. Among the many secondary battery technologies, sodium-ion batteries have an electrochemical working principle similar to that of lithium-ion batteries, that is, carriers are embedded / released in the negative electrode material and the positive electrode material, so the basic research of sodium-ion batteries has developed rapidly. In addition, sodium-ion batteries have industrial advantages such as abundant sodium reserves, low price, high safety, good rate performance, and excellent low-temperature performance, so they show great application prospects in the field of large-scale energy storage. The negative electrode material is one of the core components of sodium-ion batteries, and its properties directly affect the overall electrochemical performance of sodium-ion batteries. Among the many developed negative electrode materials, carbon materials have the advantages of high conductivity, good structural and chemical stability, and easy large-scale preparation, and have received widespread attention. Among them, hard carbon materials have the advantages of high capacity and low working voltage, becoming a hot spot and frontier in the field of sodium-ion negative electrode materials.

[0003] Coal has a series of advantages such as high carbon atom content, low cost, and abundant reserves, and is a good precursor for preparing carbon materials. The organic matter in coal mainly exhibits aromatic properties at the molecular chemical level. Direct and simple heat treatment is easily affected by π-π action to form carbon materials with a high degree of graphitization. Its small graphite interlayer spacing is not conducive to the efficient storage of large-sized sodium ions. In addition, the volatile matter in coal will introduce pore structures into the carbon materials, which will affect the sodium storage behavior of the carbon materials. Phenolic resin has the advantages of low ash content and is one of the excellent raw materials for preparing high-quality carbon materials. Coconut shell is a low-priced and widely available biomass material. After carbonization, it has a rich and developed pore structure, which is mainly micropores and macropores, and there are some mesopores. However, the larger pore structure is not conducive to the storage of sodium ions. Therefore, a simple and effective method is needed to modify its surface and structure to improve its sodium storage capacity. Summary of the invention

[0004] In order to overcome the deficiencies in the prior art, the present invention aims to provide a method for preparing a carbon material with low cost, scalable preparation, rich pore structure, and surface heteroatom doping, and its application in sodium ion batteries. Taking advantage of the low ash content and clear chemical composition of phenolic resin, coal and phenolic resin are prepared into high-performance carbon materials to achieve excellent sodium ion battery performance. In order to achieve the above-mentioned purpose of the invention and solve the problems existing in the prior art, the technical solution of the present invention is implemented as follows: The present invention provides a method for structural and chemical regulation of negative electrode carbon materials for rate-type sodium ion batteries, comprising the following steps:

[0005] (1) The raw materials are crushed and ground, and volatiles are removed through a first-stage heat treatment to obtain a precursor primary carbonization product.

[0006] (2) The primary carbonization product of the precursor is subjected to a second stage heat treatment in an active gas atmosphere to obtain a carbon material with structural etching and surface chemical modification.

[0007] (3) Under an inert atmosphere, the carbon material obtained in (2) is further subjected to a third stage of heat treatment, which involves the regulation of the microstructure and conductivity of the carbon material, and ultimately a negative electrode carbon material for a sodium ion battery is obtained.

[0008] Furthermore, the specific method is:

[0009] (1) crushing and grinding the raw materials to obtain precursor powder; placing the precursor powder in a corundum boat and placing it in a tube furnace, and pre-passing protective gas to exhaust the air in the tube;

[0010] Under the protection of argon atmosphere, carbonization is carried out at 500-900°C to obtain a precursor primary carbonization product; the raw material is one or more of coal, coal pitch, coal tar, asphalt coke, needle coke, phenolic resin, and coconut shell.

[0011] (2) replacing the protective gas with an active gas, and using the active gas to etch and dope the precursor primary carbonization product at 600-900° C. to obtain a carbon material with structural etching and surface chemical modification;

[0012] (3) The active gas is replaced with a protective gas, and the carbon material with structural etching and surface chemical modification is carbonized at a high temperature of 1000-1800° C. to obtain a negative electrode carbon material for a sodium ion battery.

[0013] The protective gas is nitrogen or argon.

[0014] The active gas is an active gas or a mixture of an active gas and an inert gas, and the active gas is one or more of NH3, water vapor, H2S, and CO2.

[0015] The flow rate ratio of active gas to inert gas in the active gas is 1:(0-10), and the total flow rate is 20-100 mL min -1 In step (1-3), the first stage heat treatment temperature is 500-900°C; the second stage heat treatment temperature is 600-900°C; the third stage heat treatment temperature is 1000-1800°C; the heating rate is 1-10°C min -1 .

[0016] The present invention also provides a half-cell prepared by using the above-mentioned carbon material, which comprises the following steps:

[0017] Negative electrode preparation: Grind 40 mg of negative electrode carbon material, 5 mg of conductive carbon black, and 5 mg of sodium carboxymethyl cellulose (CMC) in a mortar for 15 min, add 500 μL of deionized water, and grind for another 6 min to obtain a uniform slurry. Use a scraper to evenly coat the slurry on the surface of the copper foil and vacuum dry it at 120 ° C for 12 h to obtain a negative electrode sheet.

[0018] Assembly: In a glove box filled with an inert Ar atmosphere, the positive electrode shell, positive electrode sheet (sodium sheet), glass fiber diaphragm, electrolyte, negative electrode sheet, gasket, shrapnel, and negative electrode shell are stacked in order and sealed with a sealing machine. The electrolyte uses sodium hexafluorophosphate (NaPF6) as the solute and ethylene glycol dimethyl ether (DME) as the solvent, with a concentration of 1 mol L -1 The solution is used as the electrolyte to complete the battery assembly.

[0019] Test: The battery test system is a blue battery test system, and the test voltage window is 0.001~3V.

[0020] The beneficial effects of the present invention are as follows: the present invention utilizes a series of active gases containing heteroatoms such as N, O, and S to etch and dope the carbon material, thereby constructing a rich pore structure. At the same time, the introduction of heteroatoms such as N, O, and S regulates the surface chemical properties of the carbon material. Through the synergistic effect of the structure and the surface chemical properties, the carbon material achieves a high sodium storage capacity of 388.97 mAh g -1 , Coulomb efficiency is more than 90%; at 1Ag -1 At a high current density, after 200 cycles, there is 300mAh g -1 The discharge specific capacity is about 10000 mAh, showing excellent rate performance and cycle stability. Among similar methods for processing precursor materials, the method for preparing the hard carbon material for the negative electrode of a sodium ion battery provided by the present invention is simpler and easier to operate, meets the needs of large-scale industrial production, and has more excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1The hard carbon negative electrode material for sodium ion battery prepared in Example 1 is -1 First charge and discharge curve at current density.

[0022] Figure 2 The half-cell assembled with the sodium ion battery negative electrode material prepared in Example 1 is 1Ag -1 Cyclic performance test results under different current densities.

[0023] Figure 3 The hard carbon negative electrode material for sodium ion battery prepared in Example 2 is -1 First charge and discharge curve at current density.

[0024] Figure 4 The hard carbon negative electrode material for sodium ion battery prepared in Example 2 is 1A g -1 Cyclic performance test results under different current densities.

[0025] Figure 5 The hard carbon negative electrode material for sodium ion battery prepared in Example 3 is -1 First charge and discharge curve at current density.

[0026] Figure 6 The half-cell assembled with the sodium ion battery negative electrode material prepared in Example 3 is 0.05Ag -1 Cyclic performance test results under different current densities.

[0027] Figure 7 This is the rate performance test result of the half-cell assembled with the sodium ion battery negative electrode material prepared in Example 3.

[0028] Figure 8 This is a scanning electron microscope (SEM) image of the sodium ion battery hard carbon negative electrode material prepared in Example 3.

[0029] Fig. 9 The hard carbon negative electrode material of sodium ion battery prepared in comparative example is 50mAg -1 First charge and discharge curve at current density.

[0030] Fig.10 The hard carbon negative electrode material of sodium ion battery prepared in comparative example is 1A g -1 Cyclic performance test results under different current densities. DETAILED DESCRIPTION

[0031] The present invention will be further described below in conjunction with the embodiments.

[0032] Example 1

[0033] (1) Phenolic resin was crushed and ground to obtain precursor powder. The precursor powder was placed in a corundum boat and placed in the center of a tube furnace. Argon was pre-flowed for 30 minutes to remove the air in the clean tube. Under the protection of argon atmosphere, the temperature was set at 5 °C min from room temperature. -1 The heating rate was increased to 700 °C and the holding time was 2 h to obtain the primary carbonization product of the precursor.

[0034] (2) Deionized water was placed in a three-necked flask and heated by an electric heating mantle to obtain water vapor as an active gas to etch and dope the primary carbonization product of the precursor. The temperature was set at 5 °C min -1 The heating rate was raised to 800 °C and the gas flow rate was 20 mL min -1 , the holding time is 2h, and a carbon material with structural etching and surface chemical modification is obtained.

[0035] (3) The water vapor is completely replaced with argon gas, and the carbon material obtained in (2) is subjected to high temperature carbonization under the protection of argon gas atmosphere, starting from room temperature at 5 °C min -1 The heating rate was increased to 1300°C and the holding time was 2h to obtain the negative electrode carbon material for sodium ion battery.

[0036] The electrochemical performance of the hard carbon negative electrode material for sodium ion batteries prepared in Example 1 is shown in Figure 1 at 50 mA g -1 At a current density of 1.34 W, its first discharge capacity can reach 388.97 mAh g -1 , the platform capacity below 0.1V is 252.97mAh g -1 , the coulombic efficiency is 91.61% at 1Ag -1 At a high current density, it still has 298.89 mAh g after 200 cycles. -1 The discharge specific capacity shows good electrochemical performance.

[0037] Example 2

[0038] (1) Phenolic resin was crushed and ground to obtain precursor powder. The precursor powder was placed in a corundum boat and placed in the center of a tube furnace. Argon was pre-flowed for 30 minutes to remove the air in the clean tube. Under the protection of argon atmosphere, the temperature was set at 5 °C min from room temperature. -1 The heating rate was increased to 700 °C and the holding time was 2 h to obtain the primary carbonization product of the precursor.

[0039] (2) All argon gas was replaced with NH3, and the primary carbonization product of the precursor was etched and doped with active gas, starting from room temperature at 5℃min -1 The heating rate was raised to 700 °C and the gas flow rate was 20 mL min -1, the holding time is 2h, and a carbon material with structural etching and surface chemical modification is obtained.

[0040] (3) All NH3 was replaced by argon, and the carbon material obtained in (2) was carbonized at high temperature from room temperature to 5 °C min under the protection of argon atmosphere. -1 The heating rate was increased to 1300°C and the holding time was 2h to obtain the negative electrode carbon material for sodium ion battery.

[0041] The electrochemical performance of the hard carbon negative electrode material for sodium ion batteries prepared in Example 2 is shown in Figure 2 at 50 mA g -1 At a current density of 1.34 mAh g, its first discharge capacity can reach 381.27 mAh g -1 , the platform capacity below 0.1V is 253.89mAh g -1 , the first coulombic efficiency is 93.32% at 1Ag -1 At a high current density, it still has 303.17 mAh g after 200 cycles. -1 The discharge specific capacity shows good electrochemical performance.

[0042] Example 3

[0043] (1) Phenolic resin was crushed and ground to obtain precursor powder. The precursor powder was placed in a corundum boat and placed in the center of a tube furnace. Argon was pre-flowed for 30 minutes to remove the air in the clean tube. The gas flow rate was 5 L min. -1 Under argon atmosphere, the temperature was increased from room temperature to 5 °C min -1 The heating rate was increased to 700 °C and the holding time was 2 h to obtain the primary carbonization product of the precursor.

[0044] (2) All argon gas was replaced with CO2, and the primary carbonization product of the precursor was etched and doped using active gas, starting from 700℃ and 5℃min -1 The heating rate was raised to 800 °C and the gas flow rate was 20 mL min -1 , the holding time is 2h, and a carbon material with structural etching and surface chemical modification is obtained.

[0045] (3) All CO2 is replaced by argon, and the carbon material obtained in (2) is carbonized at high temperature from 800°C to 5°C min under the protection of argon atmosphere. -1 The heating rate was increased to 1300°C and the holding time was 2h to obtain the negative electrode carbon material for sodium ion battery.

[0046] The electrochemical performance of the sodium ion battery negative electrode material prepared in Example 3 is -1 At a current density of 1.34 W, its first discharge capacity can reach 379.04 mAh g -1, the first coulombic efficiency is 91.11%.

[0047] Comparative Example

[0048] (1) Phenolic resin was crushed and ground to obtain precursor powder. The precursor powder was placed in a corundum boat and placed in the center of a tube furnace. Argon was pre-flowed for 30 minutes to remove the air in the clean tube. Under the protection of argon atmosphere, the temperature was set at 5 °C min from room temperature. -1 The heating rate was increased to 700 °C and the holding time was 2 h to obtain the primary carbonization product of the precursor.

[0049] (2) The precursor primary carbonization product was heat treated in an argon atmosphere at a temperature of 5 °C min -1 The heating rate was raised to 800 °C and the gas flow rate was 20 mL min -1 The temperature holding time is 2h, and then high temperature carbonization is continued, from 800℃ to 5℃min -1 The heating rate was increased to 1300°C and the holding time was 2h to obtain the negative electrode carbon material for sodium ion battery.

[0050] The electrochemical performance of the hard carbon negative electrode material for sodium ion batteries prepared in the comparative example is -1 At a current density of 1.34 W, its first discharge capacity is 332.77 mAh g -1 , the platform capacity below 0.1V is 209.11mAh g -1 , the first coulombic efficiency is 94.40% at 1Ag -1 At a high current density, the discharge capacity after 200 cycles is 259.68 mAh g -1 Compared with the comparative example, the first discharge specific capacity in Example 1-2 is nearly 50 mAh g higher. -1 The platform capacity below 0.1V, as an important indicator for measuring the performance of hard carbon anode, has also been significantly improved, and at 1A g -1 After 200 cycles at a high current density, the discharge specific capacity of Example 1-2 is still much higher than that of the comparative example. Therefore, after the structural etching and surface chemical modification of the above-mentioned active gas, the electrochemical performance of the precursor can be significantly improved.

[0051] Although several embodiments of the present invention have been given herein, those skilled in the art should understand that the embodiments of the present invention may be modified without departing from the spirit of the present invention. The above embodiments are merely exemplary and should not be used as a limitation on the scope of the present invention.

Claims

1. A method for structural and chemical regulation of negative electrode carbon materials for rate-type sodium ion batteries, characterized in that: The steps include: (1) grinding and pulverizing a phenolic resin to obtain a precursor powder; placing the precursor powder in a corundum boat and placing the boat in a tube furnace, and pre-passing argon gas to exhaust the air in the tube; Under the protection of argon atmosphere, carbonization was carried out at 700℃ for 2h to obtain the primary carbonization product of the precursor; (2) The protective gas was replaced with an active gas, and water vapor was used as an active gas to etch and dope the precursor primary carbonization product. The temperature was 800 °C and the gas flow rate was 20 mL min -1 , the temperature holding time is 2h, and the carbon material with structural etching and surface chemical modification is obtained; (3) The argon gas is replaced by water vapor, and the carbon material with structural etching and surface chemical modification is carbonized at 1300°C for 2 hours to obtain the negative electrode carbon material for the sodium ion battery.

2. A method for structural and chemical regulation of negative electrode carbon materials for rate-type sodium ion batteries, characterized in that: The steps include: (1) grinding and pulverizing a phenolic resin to obtain a precursor powder; placing the precursor powder in a corundum boat and placing the boat in a tube furnace, and pre-passing argon gas to exhaust the air in the tube; Under the protection of argon atmosphere, carbonization was carried out at 700℃ for 2h to obtain the primary carbonization product of the precursor; (2) The protective gas was replaced with an active gas, and ammonia was used as an active gas to etch and dope the primary carbonization product of the precursor at 700 °C with a gas flow rate of 20 mL min -1 , the temperature holding time is 2h, and the carbon material with structural etching and surface chemical modification is obtained; (3) Ammonia replaces argon gas, and the carbon material with structural etching and surface chemical modification is carbonized at 1300°C for 2 hours to obtain a negative electrode carbon material for a sodium ion battery.

3. A sodium ion battery negative electrode carbon material, characterized in that: The method according to claim 1 or 2 is used to prepare the product.

4. The use of a negative electrode carbon material for a rate-type sodium ion battery according to claim 3, characterized in that: The carbon material is applied in sodium ion batteries.

Citation Information

Patent Citations

  • Sodium-ion battery negative electrode active material and preparation method and application thereof

    CN116239099A

  • Negative electrode material, preparation method thereof and sodium ion battery

    CN117352727A